DISCOURSE ANALYSIS OF DEIXIS IN PIRATES OF THE CARIBBEAN: AT WORLD’S END CONVERSATION SCRIPT - Erika Agustina; Dewi Rosnita Hardiany (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2022)
The study of language refers to a discouse analysis. Discourse analysis perform an approach of an analysis connected to language pattern of a text used in the analysis, it require linguistic competence and deixis is one of them. According to Levinson (1983), deixis devided into person deixis, place deixis, time deixis, social deixis and discourse deixis. This research aims to find all types of deixis used and the effect produced by social deixis  in the conversation script of Pirates of The Caribbean: At World’s End between all the character in the movie. The research was done using descriptive qualitative method. The data were collected from downloading the script trough a website related to the production of Pirates Caribbean movie. Then the data were classified and elaborated using Levinson five types of deixis theory and relational-absolute social diectic information. The analysis finding presented in  presentage as follows; person deixis 78,7% (as total of 607 deixis), place deixis 6,09% (as total of 47 deixis), time deixis 4,15% (as total of 32 deixis), social deixis 3,76% (as total of 29 deixis), discourse deixis 7,26% (as total of 56 deixis). As the relational-absolute social diectic information, it was found that the usage of social deixis is able to show the character relationship and hierarchy presented in the movie.Kata Kunci: discourse analysis, deixis, social deictic information, relational-absolute